The Impact of Human Resources Management Practices on Green Innovation: A Field Study at Yemeni Pharmaceutical Industrial Companies in the Capital Municipality of Sana’a - Zaid, Jamal Dirhim Ahmed; Mousa, Ragda Mohammed Abdullah (University of Science and Technology Journal for Management and Human Sciences, 2024)
The study aimed to measure the level of human resource management practices (HRMPs) and the level of green innovation achievement in Yemeni pharmaceutical companies in the Capital Municipality of Sana’a, as well as to measure the impact of human resource management practices on green innovation in the companies under study. The descriptive-analytical approach was employed, and a questionnaire was developed as the tool of data collection. The population was (1675) employees from all administrative levels in seven Yemeni pharmaceutical industrial companies in Sana’a. The questionnaire was distributed to the study sample (313) of which (240) were valid for statistical analysis. The findings revealed that the level of achievement of HRMPs in the companies under study was high, and the level of green innovation achievement was also high. The study also found that there is a significant impact of HRMP on green innovation in the companies under study, with the motivation and compensation dimension having the greatest impact on green innovation, followed by the performance appraisal dimension, and then the job design dimension. However, the study found no statistically significant impact of training and development of human resources and recruitment dimensions on green innovation. The study recommends that companies should pay more attention to the current policies followed in job design, selection and recruitment of employees, and training and development programs designed for them. In addition, companies should improve and develop compensation and incentive systems and link them to performance appraisal systems and pay more attention to environmental practices for human resource management.
Keywords: human resources management practices; green innovation; green product; green processes